2015
DOI: 10.1016/j.otsr.2015.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Complication rates and types of failure after arthroscopic acute acromioclavicular dislocation fixation. Prospective multicenter study of 116 cases

Abstract: Level of evidence 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(75 citation statements)
references
References 18 publications
3
72
0
Order By: Relevance
“…Numerous modifications of the Weaver-Dunn technique and anatomic CC reconstruction have been reported including both open and arthroscopic options 7, 8, 9, 12, 13. Despite these efforts, up to 80% of patients following AC reconstruction have been reported to lose radiographic reduction, and between 20% and 30% of patients treated surgically are reported to have complications leading to reoperation 14, 15. The goal of the presented technique is to use the biomechanical data available to create a construct that minimizes failure and provides anatomic restoration of the AC joint using a reinforced biologic construct.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous modifications of the Weaver-Dunn technique and anatomic CC reconstruction have been reported including both open and arthroscopic options 7, 8, 9, 12, 13. Despite these efforts, up to 80% of patients following AC reconstruction have been reported to lose radiographic reduction, and between 20% and 30% of patients treated surgically are reported to have complications leading to reoperation 14, 15. The goal of the presented technique is to use the biomechanical data available to create a construct that minimizes failure and provides anatomic restoration of the AC joint using a reinforced biologic construct.…”
Section: Discussionmentioning
confidence: 99%
“…12 Minimally invasive anatomic reconstruction of the AC joint is technically challenging, with complication rates of 27% to 44% reported with initial surgical techniques. 5 Complications including fractures of the clavicle or coracoid process, loss of reduction, implant failure with suture rupture, caudal migration of the supraclavicular implants, and local soft-tissue pain due to hardware or suture irritation have led to a continuous development of arthroscopically assisted techniques and implants.…”
Section: Discussionmentioning
confidence: 99%
“…12 A recent systematic review of arthroscopically assisted techniques found an overall rate of hardware irritation of 26.7%. 11 Cases of revision surgery with implant and suture removal have been described.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations